Giving peace to Europe: European geopolitics, colonial political culture, and the Hanoverian Monarchy in British North America, ca. 1740–63 - Robinson, D (Omohundro Institute of Early American History and Culture, 2016)
As William Pepperrell, the famed commander of New England's expedition against Louisbourg, was laid to rest at Kittery Point in 1759, his eulogist praised the departed general for giving peace to Europe. This sermon spoke to an influential yet scarcely studied strand of British North American public discourse, in which colonists meditated upon the workings of the eighteenth-century European state system and the developing role of the British Empire as a great power. During the tumultuous global conflicts from 1739 to 1763, British American geopolitical thinking exerted a profound influence on colonial political culture, fostering support for the Hanoverian monarchy as the “arbiter” of Europe while inspiring commensurate discourses of royalism and colonial British nationalism. However, British Americans participated in this transatlantic debate over British foreign policy on their own terms, fashioning distinctively colonial conceptions of intervention, allegiance, and nationality. These subtle expressions of Americanization, which would come to have a major impact on the imperial crisis after 1763, present a starting point for reconsidering the historical importance of this rich but little-quarried vein of colonial political culture.